The impact of innovative behavior and job satisfaction on lecturer performance at the university of Southeast Sulawesi - Hamid, Abdul; Yuniarsih, Tjutju; Disman, Disman; Santoso, Budi (ARKA INSTITUTE, 2025)
The performance of lecturers at the university level is very important to achieve goals, such as creating quality learning and developing a curriculum that provides equal opportunities for all students. Therefore, it is very important to examine the influence of innovative work practices and work ethic on lecturer performance. The purpose of this study is to understand and analyze the relationship between innovation and performance and the quality of lecturer performance. This study also seeks to identify relevant intervention models and work processes that have an impact on lecturer performance. Researchers in this study used a Likert scale questionnaire to collect data from 350 lecturers, who then took samples using the Slovin method, so that the total sample became 78 lecturers. The results of the study showed that innovative behavior significantly influenced the performance of lecturers at universities in Southeast Sulawesi. Furthermore, job satisfaction has a positive and significant effect on lecturer performance at universities in Southeast Sulawesi. It can be concluded that innovative behavior and job satisfaction affect lecturer performance.